Meaning of a public place: a story of Padang Pahlawan - Harun, Nor Zalina; Mansor, Mazlina; Said, Ismail (2013)
This paper makes a case on how the existence of padang, a public place which is commonly found in most historic cities in Malaysia, develops place meaning and place attachment amongst residents. Using mixed method approach and reviews of literature across urban design and environmental psychology disciplines, a framework for the understanding the psychological dimensions of residents' interactions with padang is demonstrated. The primary data was obtained from face to face interview (n:441) and surveys (n:165)with users of Padang Pahlawan, a demolished padang in Melaka city,Malaysia. The findings show (a) three processes and levels of place meaning; (b) the association between place meaningand place attachment; and (c) how changes of place changed people's perception and meaning to particular places. The findings suggest that residents developed deep attachments to Padang Pahlawan however change of physical character and discontinuity of place experiences have altered its meaning. This study provides substantial aspects of peopleenvironment relationship and has important implications to the task of place creation.